Postharvest evaluation, characteristics of yellow oyster mushroom (Pleurotus citrinopileatus): Physicochemical properties and antioxidant activity [Evaluasi pascapanen, karakteristik jamur tiram kuning (Pleurotus citrinopileatus): sifat fisikokimia dan aktifitas antioksidan] - Tafzi, Fitry Tafzi; AR, Nur hasnah; Indriyani, Indriyani Indriyani; Nurfaijah, Nurfaijah Nurfaijah; Wulansari, Dian wulansari; Widianti, Oktari Mia; Dameswary, Amarilia Harsanti (Jurnal Teknologi & Industri Hasil Pertanian, 2024)
The level of physiological maturity of the plant, productivity at harvest, and content in the material are all determined by harvest age, which is a component that is strongly tied to the phase of plant growth. Oyster mushrooms will undergo biochemical changes as they mature, but they will also change physically when they are harvested, especially in terms of color, texture, size, form, and the sections that may be eaten. This study aims to discover the optimal harvest age for yellow oyster mushrooms (Pleurotus citrinopileatus) based on their physical, chemical, and antioxidant activity. It also examines the impact of harvest age on the physical, chemical, and antioxidant activity of yellow oyster mushrooms (Pleurotus citrinopileatus). The design of this investigation was entirely random. This study used two harvest periods of yellow oyster mushrooms with harvest ages of 2, 3, 4, and 5 days after the appearance of pinheads as the treatment. Three times each experimental unit is repeated. The nursery, incubation, upkeep, and harvest of yellow oyster mushrooms comprised the study. The findings demonstrated that wet weight, rendemen, total phenol, and antioxidant activity of yellow oyster mushrooms were significantly influenced by harvest age. It is advised to harvest the yellow oyster mushroom on the third day after the appearance of pinheads.